P080 Audit of the Management of Sexual Assault Complainants attending Genitourinary Medicine against The British Association for Sexual Health and HIV UK National Guidelines on the Management of Adult and Adolescent Complainants of Sexual Assault 2011. (30th June 2016) - Colton, Hayley; Carr, Gemma; Garner, Anna
Abstract : Background/introduction: Patients attending clinic following an alleged sexual assault (SA) involve a complex history and management plan. The regional Sexual Assault Referral Centre (SARC) is on site and so the clinic receives significant numbers of SA referrals. As a clinic we felt that the proforma for documenting such histories was not fit for purpose. Aim(s)/objectives: To compare the documentation and management of SA complainants against standards set out by The British Association for Sexual Health and HIV UK National Guidelines on the Management of Adult and Adolescent Complainants of Sexual Assault 2011. Methods: A retrospective case note review of notes coded for SA between 1/1/13 and 31/3/14. 36 case notes were identified for inclusion. Results: 32/36 patients were female, 29/36 were heterosexual. 30/36 were of white British origin. 26/36 were referred from the local SARC. Age range 13–79 yrs. Areas which performed well in relation to the auditable outcomes were documentation in relation to: when the assault took place (100%), child protection needs (100%), who the assailant was (94%), if baseline testing occurred (94%), follow up advice (91%), what type of assault (87%). Areas which performed less well included documentation in relation to: bleeding at time of assault (8%), physical injuries (12.5%), ejaculation (24%), self harm (16%), mental state assessment (33%). Discussion/conclusion: Documentation of a number of standards requires significant improvement. Safeguarding was well managed, particularly in those under 18. As a result of gaps in documentation a SA proforma has been devised to capture all the detailed information required when assessing SA patients.